N‐Heterocyclic Carbene‐Catalyzed Umpolung of Alkynyl 1, 2‐Diketones. Issue 16 (17th July 2017) - Kong, Xiangwen; Zhang, Guoxiang; Yang, Shuang; Liu, Xiaozhi; Fang, Xinqiang
Abstract: The umpolung of alkynyl 1, 2‐diketones via N‐heterocyclic carbene (NHC) catalysis was achieved for the first time, allowing the rapid access to a large variety of synthetically and pharmaceutically important α‐pyrones under very mild conditions. A completely new NHC‐catalyzed umpolung pattern involving an O‐acylated allenolate as the key intermediate was proposed. Moreover, an unprecedented reaction pathway, featured by a series of group migrations and new bond formation, was postulated to demonstrate the formation of the products. Abstract :